Spatial analysis of rabies-transmitting animal bite cases in North Tapanuli Regency, North Sumatera Province in 2016-2020 - Simanjuntak, Saidah Fatimah Sari; Sipahutar, Tiopan; Mafkul, Martya Rahmaniati (BKM Public Health and Community Medicine, 2024)
Purpose: Rabies is a priority strategic disease because it has an impact on socio-economic and public health. This study aims to describe the incidence of rabies-transmitting animal bite cases in North Tapanuli Regency in 2016-2020, contribute to understanding the dynamics of cases, and provide effective information in controlling cases of animal bites that transmit rabies. Methods: Ecological study using aggregated data. The data was collected from monthly reports of rabies cases at the North Tapanuli Regency Health Service in 2016-2020. As a unit analysis, all districts are used. QGIS and GeoDA software are used for data analysis. Through GeOda software, spatial autocorrelation analysis was carried out globally using Moran's I test and locally using the LISA test. Results: Rabies-transmitting animal bite cases had a dispersed pattern in 2016 (I<E[I]) and a clustered pattern (I>E[I]). Globally, there is positive spatial autocorrelation in rabies-transmitting animal bite cases between districts in North Tapanuli Regency in 2017 and 2020 (p-value < 0.05). Moran's cluster map shows that locally in 2016-2020, the districts in the quadrant I (High-High) are Siborongborong and Sipoholon. Quadrant II (Low-High) is Adiankoting and Pagaran. Quadrant III (Low-Low) is Pangaribuan, and quadrant IV (High-Low) is Pahae Jae and Pangaribuan. Conclusion: Globally, cases of animal bites that transmit rabies in North Tapanuli Regency occur in clusters. It means that the number of bite cases in one area is related to the number of cases in other nearby areas. Therefore, rabies control program interventions in areas with high observation values must be prioritized so they do not spread to areas with low observation values.